Status and future of the soft X-ray free-electron laser beamline at the SHINE - Liu, Tao; Huang, Nanshun; Yang, Hanxiang; Qi, Zheng; Zhang, Kaiqing; Gao, Zhangfeng; Chen, Si; Feng, Chao; Zhang, Wei; Luo, Hang; Fu, Xiaoxi; Liu, He; et al. (Frontiers in Physics, 2023)
The Shanghai High repetition rate XFEL and Extreme light facility (SHINE) is under construction and aims at generating X-rays between 0.4 and 25 keV with three FEL beamlines at repetition rates of up to 1 MHz. The soft X-ray FEL beamline, FEL-II, will be ready for commissioning in 2025. It is designed to cover the photon energy from 0.4 to 3 keV, in which the baselines of the FEL operation modes are self-amplified spontaneous emission (SASE), self-seeding, echo-enabled harmonic generation (EEHG), and polarization control. Therefore, a high repetition-rate external seed laser, large period length modulator, soft X-ray monochromator, planar undulator, and elliptically polarized undulator have been adopted in the FEL-II beamline. Several potentials such as an ultra-short pulse mode and a multi-color mode are also foreseeable without significant equipment changes in the follow-up operation. A dual-period undulator design is suggested for the echo-enabled harmonic generation (EEHG) commissioning, and it has great potential to break through the unreachable energy of the fully coherent X-ray in the future. The FEL-II beamline will deliver SASE radiation and fully coherent radiation in all the wavelengths of interest.